Effect of comparison ratio of additives on changes in pH levels, TSS, Fe, and Mn metals in the acid mine water treatment process at KPL BB 13 PT bukit asam, tbk. - Enggal Nurisman; Tree Silvia Putri Minata; Shenia Meidina (Chemical Engineering Department, Faculty of Engineering, Universitas Sriwijaya in collaboration with Asosiasi Pendidikan Tinggi Teknik Kimia Indonesia (APTEKIM), 2023)
Mining activities with an open system at PT Bukit Asam Tbk. have the potential to produce acid mine drainage due to contamination by rocks with sulfur content. Acid mine drainage treatment is carried out by the active method in the Mud Settling Pond (KPL). Addition of alum (Al2(SO4)3) and quicklime (CaO) to increase pH levels and reduce water turbidity. Management is carried out to meet environmental quality standards, namely with a pH value of 6-9, a maximum TSS value of 400, and for Mn and Fe a maximum of 4 and 7 mg/L, respectively. Jar Tests were conducted on samples from KPL BB-13 with mixed doses of alum and quicklime used were 0.02 and 0.10 grams; 0.03 and 0.12 grams; 0.04 and 0.14 grams; 0.05 and 0.16; 0.06 and 0.18; and 0.7 and 0.20. The best test results are at a mixed dose of 0.02 grams of alum and 0.10 grams of quicklime to obtain a pH value of 7 (neutral), besides that TSS and Fe metal levels have decreased. Mn metal also decreased, but did not meet environmental quality standards. Increased doses for field scale under actual conditions of observation required alum as much as 1.00 g/s and quicklime as much as 5.0052 g/s. The evaluation results show that the acid mine drainage treatment carried out by the company is more effective and efficient than the dose of laboratory test results.